2012
DOI: 10.1038/nature11358
|View full text |Cite
|
Sign up to set email alerts
|

More extreme swings of the South Pacific convergence zone due to greenhouse warming

Abstract: The South Pacific convergence zone (SPCZ) is the Southern Hemisphere's most expansive and persistent rain band, extending from the equatorial western Pacific Ocean southeastward towards French Polynesia. Owing to its strong rainfall gradient, a small displacement in the position of the SPCZ causes drastic changes to hydroclimatic conditions and the frequency of extreme weather events--such as droughts, floods and tropical cyclones--experienced by vulnerable island countries in the region. The SPCZ position var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
180
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 28 publications
(51 reference statements)
7
180
1
Order By: Relevance
“…Recent modeling work (e.g., Cai et al, 2012) has demonstrated the possibility for warmer surface conditions to produce more extreme equatorward movement of the SPCZ during interannual variability, producing more interannual, El Niño-Southern Oscillation (ENSO)-related drought at our study site. Given our lack of ability to consistently resolve interannual variability in the stalagmite record, we cannot address interannual changes in the SPCZ that may be related to anthropogenic forcing.…”
Section: Stalagmite Variability: External Forcing Vs Internal Variabmentioning
confidence: 95%
“…Recent modeling work (e.g., Cai et al, 2012) has demonstrated the possibility for warmer surface conditions to produce more extreme equatorward movement of the SPCZ during interannual variability, producing more interannual, El Niño-Southern Oscillation (ENSO)-related drought at our study site. Given our lack of ability to consistently resolve interannual variability in the stalagmite record, we cannot address interannual changes in the SPCZ that may be related to anthropogenic forcing.…”
Section: Stalagmite Variability: External Forcing Vs Internal Variabmentioning
confidence: 95%
“…3e) is still dominated by a drying of the SPCZ, but rainfall increases in the western Pacific region between 0−10 • S, consistent with the notion that regions warming most become wetter and regions that warm least become drier 20 . This mean northeastward shift of the SPCZ is reminiscent of the zonal SPCZ events that have occurred together with some strong El Niño events 13,40 .…”
Section: T He Observed Spcz (Ref 1) Extends From the Tropical Westernmentioning
confidence: 96%
“…1b). A reduced meridional SST gradient 13 between 0 − 15 • S causes the rainfall increase at the Equator while a larger zonal SST gradient 21 in the eastern tropical South Pacific between 10 • S and 20 • S leads to an intensification of the southeasterly trade winds in this region 26 , thus enhancing transport of dry air towards the eastern side of the SPCZ.…”
Section: T He Observed Spcz (Ref 1) Extends From the Tropical Westernmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The anomalous conditions caused severe Page 3 of 14 rainfall deficits in the western Pacific and the Maritime Continent, devastating hurricanes in the central tropical Pacific region (where such phenomena are extremely rare 4,8,10,11 ), and the disappearance of marine life and decimation of the native bird population on Christmas Island 17,18 . The high SSTs led to severe bleaching of corals in the Pacific and beyond 5,6 , including the 1998 mass mortality of corals on lagoonal reefs in Belize -the first time a coral population in the Caribbean collapsed completely from bleaching 6 .…”
mentioning
confidence: 99%